Mental Health Social Work Reimagined - Cummins, Ian, 1961- (Book collections on Project MUSE., 2019)
"This much-needed book calls for a return to mental health social work that has personal relationships and an emotional connection between workers and those experiencing distress at its core." -- Provided by publisher.